Dimenzije mehanizacije in vozil, ki se gibljejo po slovenskih gozdovih zunaj gozdnih cest - Saražin, Jaša (Acta silvae et ligni, 2022)
The Forest Act allows vehicles to be driven in the forest outside of forest roads for the purpose of forest management or rescue of persons or property. The vehicles and machinery intended for these tasks are very diverse, both in their form and in the dimensions and quality requirements of the thoroughfares on which they move. The types of mechanization discussed include agricultural tractors, specialized forestry mechanisation, trailers on tractors, trucks, cars and construction machinery. By reviewing various databases, legal restrictions and our own experience, interval data on the mass and width of representative examples of each category were given. It was estimated that among forest owners, the most numerous mechanization was up to 200 cm wide, while among professional contractors and protection and rescue forces, the most numerous mechanization and vehicles were up to 230 cm wide. It was also found that mechanization and vehicles up to 230 cm wide can perform all forest management and protection and rescue tasks at least on a basic scale.
Keywords: agricultural tractors; forestry mechanization; gozdarska mehanizacija; kmetijski traktorji; priklopniki; prometnice; protection and rescue; thoroughfares; tovorna vozila; tractor attachments; trailers; traktorski priključni stroji; trucks; zaščita in reševanje